2022
DOI: 10.3390/agriculture12101522
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Deficit Irrigation on Yield Components and Chemical Composition of Albariño Grapes Grown in Galicia, NW Spain

Abstract: In the context of climate change, water management is crucial for controlling the reproductive growth and quality of grapes. In this study, we aim to determine the effects of different water regimes on the yield components and chemical composition of grape Vitis vinifera Albariño grown in Galicia. Four treatments were tested in the trial: rainfed (T0), irrigated at 30% of ETo from veraison to harvest (T1), from pea-size to harvest (T2), and throughout the whole vegetative cycle (T6). To analyse the effects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
0
1
0
Order By: Relevance
“…Thus, this effect on minority varieties has recently been considered [13], whose results revealed that some of the traditional varieties, cultivated under moderate and severe water stress conditions, are capable of maintaining productions with an adequate phenolic composition, similar to or even more favourable than other varieties more widespread. In the same line, various authors have observed a strong influence on the accumulation of volatiles compounds in different widely cultivated varieties due to the environmental factors, such as water availability, being positively or negatively affected by water stress depends on the family of compounds under study [14][15][16][17]. Nevertheless, the response of volatile composition to water deficit in a great number of recently recovered minority varieties remains unknown.…”
Section: Introductionmentioning
confidence: 97%
“…Thus, this effect on minority varieties has recently been considered [13], whose results revealed that some of the traditional varieties, cultivated under moderate and severe water stress conditions, are capable of maintaining productions with an adequate phenolic composition, similar to or even more favourable than other varieties more widespread. In the same line, various authors have observed a strong influence on the accumulation of volatiles compounds in different widely cultivated varieties due to the environmental factors, such as water availability, being positively or negatively affected by water stress depends on the family of compounds under study [14][15][16][17]. Nevertheless, the response of volatile composition to water deficit in a great number of recently recovered minority varieties remains unknown.…”
Section: Introductionmentioning
confidence: 97%
“…Thus, this effect on minority varieties has recently been considered [ 13 ]; the results revealed that some of the traditional varieties, cultivated under moderate and severe water stress conditions, are capable of maintaining productions with an adequate phenolic composition, similar to or even more favorable than other varieties more widespread. In the same line, various authors have observed a strong influence on the accumulation of volatile compounds in different widely cultivated varieties due to environmental factors, such as water availability, being positively or negatively affected by water stress depending on the family of compounds under study [ 14 , 15 , 16 , 17 ]. Nevertheless, the response of volatile composition to water deficit in a great number of recently recovered minority varieties remains unknown.…”
Section: Introductionmentioning
confidence: 99%